Zooarchaeology of the Pre-Bell Beaker Chalcolithic Period of Barrio del Castillo (Torrejón de Ardoz, Madrid, Spain) - Verónica Estaca-Gómez; Mónica Major-González; Jorge Cañas-Martínez; José Yravedra (Heritage)
This article presents the first results of the zooarchaeological analysis of Chalcolithic levels of the Barrio del Castillo site (Torrejón de Ardoz), located within the Aldovea complex, which also contains evidence from other prehistoric periods. The Barrio del Castillo sector reveals an occupation pattern characterized by pit and silo fields, a common phenomenon in the Tagus Middle Valley’s Prehistory. This study focuses on the Chalcolithic phase, which exhibits two types of faunal accumulations: one linked to domestic activities (referred to as domestic assemblages), and another with a more symbolic character, involving the burial of articulated or semi-articulated animals, mainly dogs, designated as ritual deposits. The first type of accumulation is dominated by domestic species like caprines (sheep and goats) and cattle. Other domestic species, like pigs and dogs, alongside wild species, like horses and deer, appear in smaller quantities. On the other hand, ritual deposits are largely dominated by dogs in the Chalcolithic phase. This paper emphasizes the marked contrast between the two types of accumulations, domestic and ritual, and highlights the implications that these might have toward a better understanding of the world of the first metallurgical communities of the inner Iberian Peninsula.